New mechanistic insights of anti-obesity by sleeve gastrectomy-altered gut microbiota and lipid metabolism - Liu, Chuxuan; Xu, Qian; Dong, Shuohui; Ding, Huanxin; Li, Bingjun; Zhang, Dexu; Liang, Yongjuan; Li, Linchuan; Liu, Qiaoran; Cheng, Yugang; Wu, Jing; Zhu, Jiankang; et al. (Frontiers in Endocrinology, 2024)
The obesity epidemic has been on the rise due to changes in living standards and lifestyles. To combat this issue, sleeve gastrectomy (SG) has emerged as a prominent bariatric surgery technique, offering substantial weight reduction. Nevertheless, the mechanisms that underlie SG-related bodyweight loss are not fully understood.In this study, we conducted a collection of preoperative and 3-month postoperative serum and fecal samples from patients who underwent laparoscopic SG at the First Affiliated Hospital of Shandong First Medical University (Jinan, China). Here, we took an unbiased approach of multiomics to investigate the role of SG-altered gut microbiota in anti-obesity of these patients. Non-target metabolome sequencing was performed using the fecal and serum samples.Results: Our data show that SG markedly increased microbiota diversity and Rikenellaceae, Alistipes, Parabacteroides, Bactreoidales, and Enterobacteraies robustly increased. These compositional changes were positively correlated with lipid metabolites, including sphingolipids, glycerophospholipids, and unsaturated fatty acids. Increases of Rikenellaceae, Alistipes, and Parabacteroide were reversely correlated with body mass index (BMI).In conclusion, our findings provide evidence that SG induces significant alterations in the abundances of Rikenellaceae, Alistipes, Parabacteroides, and Bacteroidales, as well as changes in lipid metabolism-related metabolites. Importantly, these changes were found to be closely linked to the alleviation of obesity. On the basis of these findings, we have identified a number of microbiotas that could be potential targets for treatment of obesity.